2013
DOI: 10.1096/fj.13-227298
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐mediated oxidation of erythrocyte peroxiredoxin 2 as a potential marker of oxidative stress in inflammation

Abstract: Peroxiredoxin 2 (Prx2) is an abundant thiol protein in erythrocytes. It is oxidized readily on exposure to hydrogen peroxide (H2O2) and provides antioxidant protection by cycling between its reduced and disulfide-bonded forms. To test whether Prx2 oxidation could occur in pathological situations where neutrophils are activated, we exposed human erythrocytes to stimulated neutrophils and measured Prx2 oxidation by immunoblotting of nonreducing gels. With phorbol myristate acetate, lipopolysaccharide or Staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…It has been reported that the hyperoxidized forms of Prx family proteins can be found in neuronal cells [7], the brains of patients with Alzheimer's disease [8], patients with asthma [9] and patients with sepsis [10]. Additionally, Prx2 has been reported to be aberrantly expressed in several cancer cell lines [11][12][13][14].…”
Section: .Introductionmentioning
confidence: 99%
“…It has been reported that the hyperoxidized forms of Prx family proteins can be found in neuronal cells [7], the brains of patients with Alzheimer's disease [8], patients with asthma [9] and patients with sepsis [10]. Additionally, Prx2 has been reported to be aberrantly expressed in several cancer cell lines [11][12][13][14].…”
Section: .Introductionmentioning
confidence: 99%
“…Similar observations are found when we correlated SOD activity with SOFA (Figure C) and APACHE II (Figure D). Another important antioxidant enzyme CAT which is associated with the H 2 O 2 destruction, thereby, protects the cells and tissues from H 2 O 2 ‐mediated toxicity . Catalase activity's antioxidant action come into the picture when free radicals circulate into the bloodstream via erythrocyte catalase, where it prevents meta‐haemoglobin accumulation and finally degrades H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Peroxiredoxins have been recently reviewed as biomarkers of oxidative stress [65], which is considered one cause of pathogenic mechanisms in neurological diseases. In particular, oxidation of PRDX2 was described to occur in pathological situations and inflammation where neutrophils are activated [66]. PRDX2 has been reported contributing to neuroprotection and was proposed for treatment for neurodegenerative diseases [67].…”
Section: Discussionmentioning
confidence: 99%